Pengaruh Terapi Accupressure Dengan Menggunakan Minyak Zaitun Terhadap Penurunan Fatigue Pada Pasien Dengan Chronic Kidney Disease (CKD) Di Ruang Kenanga RSUD dr. Haryoto Lumajang - Vidia Puspita Sari; R Endro Sulistyono; Ainul Yaqin Salam; Suhari Suhari (Journal of Innovative and Creativity, 2025)
Chronic Kidney Disease (CKD) is a clinical syndrome caused by a decline in kidney function. Fatigue in CKD patients occurs due to the kidneys’ inability to produce sufficient erythropoietin (EPO), a hormone necessary to stimulate red blood cell production. This results in decreased oxygen levels in the body, causing fatigue, weakness, and lethargy. Non-pharmacological therapies such as acupressure and olive oil application can stimulate the nervous system and improve energy flow in the body, which help reduc fatigue. This study used a pre-experimental design with a One-Group Pretest and Posttest Design. The Chi-Square test was used for data analysis. The sample consisted of 29 respondents selected through accidental sampling. The intervention involved applying acupressure to specific points on the body of CKD patients hospitalized in the Kenanga Room of dr. Haryoto Lumajang Public Hospital. The intervention was conducted over 3 days, with 3 sessions per day, each lasting 20 minutes. Before the acupressure and olive oil intervention, 7 respondents (24.1%) experienced mild fatigue and 22 respondents (75.9%) experienced severe fatigue. After the intervention, 20 respondents (69%) reported mild fatigue and 9 respondents (31%) still experienced severe fatigue. The results showed a p-value of 0.042 (< 0.05), indicating that the alternative hypothesis (Ha) is accepted. This means there was a significant difference before and after the acupressure combined with olive oil therapy in CKD patients at dr. Haryoto Lumajang Public Hospital. Based on these findings, it is recommended that hospitals, nurses, and patients consider acupressure and olive oil as non-pharmacological therapy options for patients experiencing fatigue.